Canine prostate specific esterase (CPSE) as an useful biomarker in preventive screening programme of canine prostate: CPSE threshold value assessment and its correlation with ultrasonographic prostatic abnormalities in asymptomatic dogs. (22nd November 2017) - Alonge, S; Melandri, M; Leoci, R; Lacalandra, GM; Aiudi, G
Contents: Due to the increased attention that pet‐owners devote to their animals and to the improved veterinary care, investigations regarding methods to early detect prostatic disorders that might affect canine life quality have been performed. Canine prostate specific esterase (CPSE) concentration was reported to be higher in dogs suffering from prostatic diseases. This study aimed to estimate the CPSE threshold as a biomarker to early identify prostatic diseases in asymptomatic dogs. The ultrasonographic examination of the prostate was performed in 19 dogs (6–40 kg; 1–5 years) with no symptoms of prostatic diseases. Dogs were grouped according to the presence (Group A) or absence (Group B) of prostatic disorders at the ultrasound (altered appearance, the presence of cysts or irregular borders). For each dog, a venous blood sample was collected to measure serum CPSE and the ratio between calculated and normal expected prostatic volume was assessed for each dog. The CPSE data were statistically analysed ( t test, p  < .05), and the CPSE threshold in blood serum between groups was calculated by ROC. In 11 dogs, ultrasonography showed signs of prostatic abnormalities (Group A, 2–5 years), while no signs were detected in eight dogs (Group B, 1–3 years). The calculated/estimated volume ratio resulted greater than 1.5 in Group A dogs. The CPSE was statistically different between groups ( p  < .0001): higher in Group A (mean = 184.9, SD  = 126 ng/ml) than in Group B (38.9 ± 22.1 ng/ml). The cut‐off CPSE threshold was 52.3 ng/ml (ROC, AUC = 0.974, SE 95.6%, SP 89.2%). This study suggests that CPSE serum concentration higher than 50 ng/ml in asymptomatic dogs is associated with ultrasonographic alterations and increased the prostatic size (volume by 1.5 times greater than the normal size). As the onset of prostatic disorders often remains asymptomatic, the rapid assessment of CPSE could be suitable for selecting preventively those animals that would require further accurate evaluation.